2016
DOI: 10.1371/journal.pone.0153113
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BRCA1 Deficiency Using Multi-Analyte Estimation of BRCA1 and Its Repressors in FFPE Tumor Samples from Patients with Triple Negative Breast Cancer

Abstract: PurposeApart from germ-line BRCA1-mutated breast cancers, a significant proportion of women with sporadic triple negative breast cancer (TNBC) sub-type are known to harbour varying levels of BRCA1-dysfuction. There is currently no established diagnostic method to identify these patients.MethodsThe analysis was performed on 183 primary breast cancer tumor specimens from our longitudinal case-series archived as formalin-fixed-paraffin-embedded (FFPE) blocks comprising 71 TNBCs and 112 Hormone receptor positive H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…In the study by Al-Mula et al, the same weak correlation was found between IHC protein evaluation and mRNA levels quantification, using real-time RT-PCR [42]. Reported correlations with epigenetic inactivation through promoter hypermethylation varied, from good correlations in high-grade ovarian serous carcinoma [43] to weak in BC [44]. BRCA1 IHC evaluation suffers from considerable run-to-run variability [41].…”
Section: Introductionmentioning
confidence: 93%
“…In the study by Al-Mula et al, the same weak correlation was found between IHC protein evaluation and mRNA levels quantification, using real-time RT-PCR [42]. Reported correlations with epigenetic inactivation through promoter hypermethylation varied, from good correlations in high-grade ovarian serous carcinoma [43] to weak in BC [44]. BRCA1 IHC evaluation suffers from considerable run-to-run variability [41].…”
Section: Introductionmentioning
confidence: 93%
“…The majority of the literature is based on Crippa et al (2014) ID4 expression is inversely correlated with miR-342 and (Turner et al 2007, Thike et al 2015, Korlimarla et al 2016. Beger and coworkers (2001) subsequently characterised the regulators of BRCA1 gene expression and identified ID4 as an upstream regulator of the BRCA1 promoter using an inverse genomics approach in luminal breast cancer cell lines.…”
Section: Id4 and Brca1 In Blbcmentioning
confidence: 99%
“…[5][6][7][8][9] As the evaluation of gene abnormalities by IHC is limited, genetic analysis methods, such as fluorescence in situ hybridization and polymerase chain reaction (PCR), have been increasingly used in the detection of point mutations, insertion/deletions, and formation of fusion genes. [10][11][12][13][14][15][16][17][18][19][20] In addition, there are diverse types of cancer-specific target molecules, and a large number of molecular target drugs have been developed and used clinically. Hence, cancer prognosis has significantly improved.…”
Section: Introductionmentioning
confidence: 99%